Utilization of rapid prototyping technology for the fabrication of an orthopedic shoe inserts for foot pain reprieve using thermo-softening viscoelastic polymers: A novel experimental approach. (March 2020) - Sharma, Shubham; Singh, Jujhar; Kumar, Harish; Sharma, Abhinav; Aggarwal, Vivek; Gill, Amoljit Singh; Jayarambabu, N; Kailasa, Saraswathi; Rao, K Venkateswara
This research work has been completed by concentrating on the structure of inserts for foot orthosis fabricated by utilizing rapid prototyping technology. Thermoplastic elastomer and thermoplastic polyurethane are the most commonly used materials that are being used in customized three-dimensional printed orthotic insoles, which are comfortable and prevent the user in many foot disorders. Thermo-softening viscoelastic polymers, explicitly Filaflex and Ninjaflex, have been printed by utilizing Flash Forge three-dimensional printers to evaluate the mechanical properties of specimens with alterations of the percentage rate fill-up design replicas. The results are compared on the basis of hardness test, flexural/bending test, and tensile test using Durometer and Universal Testing Machine (UTM). It has also been observed that the most significant effecting factor is infill density.